ENGLISH TEACHER PERSONALITY TOWARD THE MOTIVATION IN ENGLISH LEARNING BY THE ELEVENTH GRADE STUDENTS OF SMK KRISTEN MAKALE - Judith Ratu (Teaching English as a Foreign Language Overseas Journal, 2016)
The objective of the research was to know the English Teacher Personality towardMotivation in English Learning by the Eleventh Grade Students of SMK Kristen Makale.In doing this researcher, the researcher used quantitative method. The population of thisresearch is the eleventh grade students of SMK Kristen Makale academic year 2016/2017which consist of 86 students and divided into four classes. This research employs arandom sampling where the researcher took only 40 students as respondents. Theinstrument that used by the researcher in collecting data is questionnaire. Based on thedata analysis, the researcher found that there are 12 items of English teacher personalitythat motivated students they are: (1) English teacher that explain the material whilestanding in front of the classroom, (2) Walking around in the classroom to watch his/herstudents, (3) Explain the material put in between humor in the classroom, (4) Firm inteaching, (5) Giving opportunity for students in expressing the students’ idea about thetopic, (6) On time to teach in classroom, (7) Evolving the material, (8) Answering directlythe students’ question about the material, (9) Making homework from the students’question about the material, (10) saying you can do it! when students do the difficulttask, (11) Giving commendation to students when they get high school grade, and (12)Giving spirit to the students when they get low school grade. Whereas, there are 8 itemsof English teacher personality that unmotivated students they are: (1) English teacher thatexplain the material while sitting on his/her chair, (2) Sitting on his/her chair while givingthe test, (3) Beginning the lesson to the main topic, (4) Coming late to teach in classroom,(5) Absent and give students confidence to do exercises until the end of lesson, (6) absentand give students confidence to discuss the material until the end of lesson, (7) Explainthe material based on the book, and (8) saying What do you have done so far is so good!when student get low school grade.